Perancangan Antarmuka Sistem Informasi Akademik Mahasiswa Berbasis Perangkat Bergerak - Muhammad Fadhil; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Universitas Brawijaya is one of many educational institutions that have implemented information technology to support the academic process successfully. Even though they had provided an adequate information portal, the system provided by Universitas Brawijaya has various problems, limitations and shortcomings. One of the problems found in the system is when the system is accessed through a mobile device. To solve various problems that exist in the system, especially those related to Usability, Design Thinking techniques are used to find suitable solutions to correct existing problems. Design Thinking is a methodology is used to define problems and produce solutions. This methodology is chosen because its ability to define problems and explore solutions that can solve said problems. Data obtained from the Design Thinking process is supported by data obtained from Usability testing which was also used during this study. The result of this study is a prototype that functions like the final system would. Existing prototype can be used as a basis for the organization to implement the resulting solutions so that the problems experienced by users while accessing the system can be minimized. The final prototype produced effectively reduce user task completion time by 59.12%.